Establishment of the novel bivalve body plan through modification of early developmental events in mollusks. Issue 6 (14th April 2020) - Wada, Hiroshi; Phuangphong, Supanat; Hashimoto, Naoki; Nagai, Kiyohito
Abstract: Mollusks have a wide variety of body plans, which develop through conserved early embryogenesis, namely spiral embryonic development and trochophore larvae. Although the comparative study of mollusks has attracted the interest of evolutionary developmental biology researchers, less attention has been paid to bivalves. In this review, we focused on the evolutionary process from single‐shell ancestors to bivalves, which possess bilaterally separated shells. Our study tracing the lineage of shell field cells in bivalves did not support the old hypothesis that shell plate morphology is due to modification of the spiral cleavage pattern. Rather, we suggest that modification of the shell field induction process is the key to understanding the evolution of shell morphology. The novel body plan of bivalves cannot be established solely via separating shell plates, but rather requires the formation of additional organs, such as adductor muscles. The evolutionary biology of bivalves offers a unique view on how multiple organs evolve in a coordinated manner to establish a novel body plan. Abstract : RESEARCH HIGHLIGHTS: Various morphology of mollusks developed from the conserved spiral development provide a nice research area of EvoDevo. Unique shell plate morphology is likely to be achieved through modification of the shell field induction process. The evolutionary biology of bivalves offers a unique view on how multiple organs evolve in a coordinated manner to establish a novel body plan.